The Effect of Open and Closed-Skill Sports on Cognitive Functions - Serkan Pancar (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2020)
This study aimed to compare amateur athletes' cognitive function performances in table tennis, an open-skill sport requiring close attention and cognitive function, and athletes, a closed-skill sport where environmental stimuli do not change. This study included 28 table tennis players (mean age: 19.82 3.90 years, mean height: 175.10 7.04 cm), 23 athletes (mean age: 20.60 .03 years, mean height: 171.30 8.37 cm), 22 Sedentary (mean age: 18.86 4.16 years, mean height: 174.91 7.62 cm), a total of 73 volunteers participated. Trail Making Tests (A and B) were applied to determine the participants' cognitive function levels. Part A measures cognitive characteristics such as motor processing speed, number sequencing (A time), and part B measures cognitive characteristics such as attention, set changing ability, cognitive flexibility (B time). The application was conducted in a quiet, noiseless environment with only the researcher and the participant. The completion times of the test were recorded in seconds. "SPSS22.0" statistical package program was used in the analysis of the data. In examining the statistical difference between independent groups in categorical data analysis, the Kruskal Wallis test was used. Tamhane post hoc test was applied to determine the difference between groups. Significance level <.05 was selected. In the Kruskal Wallis test comparisons, no significant difference was found between the groups in terms of Trail Making Test A times (p> 0.05). In contrast, a statistically significant difference was found between the groups in terms of the trail, making test B times (p <0.05). In the post hoc comparisons, a statistically significant difference was found between the table tennis-athletes and table tennis-control groups in the B part of the trail making test (p <0.05). However, there was no significant difference between athletes and control groups (p> 0.05). In line with the findings obtained from the study, it was determined that the executive function performances of young individuals who do open-skill exercises were better than the closed-skill and control groups.